The contour method for residual stress determination applied to an AA6082-T6 friction stir butt weld - Richter-Trummer, Valentin (2011)
Residual stresses parallel to the welding direction on a cross-section of a 3 mm thick friction stir butt-welded aluminium alloy AA6082-T6 plate were determined using the contour method. This is a destructive relaxation based measurement technique capable of determining the full- eld residual stresses perpendicular to a plane of interest. A wire electro discharge machining cut was performed revealing the plane of interest. The residual stresses present before the straight cut lead to a deformed cutting plane. Then, a coordinate measuring machine was used to acquire the cutting plane shape of both plate halves after the cut. A data reduction scheme for noise and error elimination was used. The measured deformation was applied to a linear elastic nite elements model considering the real specimen geometry. A full contour map of longitudinal residual stresses on a weld cross section was determined in this way, revealing detailed information on the residual stress distribution in the inside of a friction stir weld, especially in the nugget zone. A typical M-shape, usually described for the residual stress distribution in friction stir welds, was found. The maximum residual stresses are below the yield strength of the material in the shoulder region and, outside of the welding region, low tensile and compressive residual stresses are responsible for the necessary stress equilibrium on the plane of interest. A comparison was made with the established incremental hole drilling technique on an equivalent plate for validation and good agreement of both techniques was obtained. The distribution, as well as the magnitude of the residual stresses measured by both techniques, is very similar, thus validating both the experimental and numerical procedures used for the contour method application, which is presented and discussed in the paper.